COMMUNITY PARTICIPATION IN ACCELERATING BEHAVIOR CHANGE IN HANDLING COVID-19 - Mahmudah, Rifatul; Imelda, Johanna Debora (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Community participation is essential for the sustainability of a policy or program. The World Health Organization (WHO) suggested the importance of community participation in handling the Corona Virus Disease 2019 (Covid-19) pandemic. Behavioural change by implementing health protocol is believed to be a crucial step to control the pandemic. By involving community participation, the effort to accelerate behavioral change will be more sustainable. This paper is a literature review that explains the concept of community participation. This pieace is also pointed out determinants that need to be considered in increasing community participation. The determinants are are effective government, proper definition regarding the related issues, and voluntary and access.